HUMAN RESOURCE PERFORMANCE INDICATORS BASED ON THE PERSPECTIVE OF LEARNING AND GROWTH IN THE BALANCED SCORECARD METHOD AT PUSKESMAS 4 ULU IN 2017 - Endah Widya Purnamasari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The aim of this research is arranging human resource performance indicator by learning and growth perspective in balanced scorecard method at 4 Ulu Health Center Palembang City. This research is a qualitative research by using case study approach. The populations are all of workers of 4 Ulu Health Center Palembang City. And the samples are permanent workers in 4 Ulu Health Center Palembang City. And the samples are permanent workers in 4 Ulu Health Center Palembang City. The steps of this research are literature study, internal meeting to key informants, first step of questionnaires spreadsheet, second step of questionnaires spreadsheet and recommendation indicators measurement. As result of this research, the most relevant and important human resource indicator which is used to assess human resource performance in 4 Ulu Health Center Palembang City are work quality of human resources indicator, human resource involvement in decision making indicator, skill indicator, turn over ratio indicator, and worker’s absence indicator.